Institute of Astronomy of Kharkiv V. N. Karazin National University - (:unkn) unknown (Kharkiv : Kharkiv V. N. Karazin National University, 2009)
In 2008 Ukrainian astronomical community has commemorated 200 anniversary of astronomy in Kharkiv. This brochure is devoted to this anniversary and presents information on the Institute of Astronomy of Kharkiv V. N. Karazin National University. This is a compilation of inputs from different research groups and individuals of the Institute. The Report covers the staff and its activities including also a highlight reference list of publications. A short overview of the Institute history and the current status of its scientific activity are given.

У 2008 році українська астрономічна спільнота відзначила 200-річчя астрономії в Харкові. Ця брошура представляє інформацію про Інститут астрономії Харківського національного університету імені В. Н. Каразіна. Це збірка матеріалів різних дослідницьких груп та окремих осіб Інституту. Звіт охоплює співробітників та його діяльність, а також містить ключовий список використаної літератури. Наведено короткий огляд історії Інституту та сучасного стану його наукової діяльності.
Keywords: Institute of Astronomy of V. N. Karazin National University; Kharkiv V. N. Karazin National University; Lunar Studies; Asteroids and Comets; Space Telescope; Jupiter’s Atmosphere; Solar Studies; Gravitational lenses; SOCIAL SCIENCES::Social sciences::Education